2022
DOI: 10.1002/ccr3.6280
|View full text |Cite
|
Sign up to set email alerts
|

Incidental finding of maternal malignancy in an unusual non‐invasive prenatal test and a review of similar cases

Abstract: We present a clinical case where a complex abnormal non-invasive prenatal test (NIPT) result in a research project revealed carcinoma of the breast in the pregnant woman. Furthermore, the NIPT result did not demonstrate the same fetal chromosomal aberration as the chorion villus sample. A literature search for similar cases was performed identifying 43 unique cases, where abnormal NIPT results were related to maternal malignancy. Malignancy is a rare but important cause of complex abnormal non-invasive prenata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Looking back, this is primarily an issue in the rare cases where mosaicism for sex‐chromosome disorders or mosaicism for CNVs are detected. Over time, we investigated how culturing may affect the aberrations 16 , 17 and, here, simultaneous DNA analyses and culturing would have facilitated learning.…”
Section: Discussionmentioning
confidence: 99%
“…Looking back, this is primarily an issue in the rare cases where mosaicism for sex‐chromosome disorders or mosaicism for CNVs are detected. Over time, we investigated how culturing may affect the aberrations 16 , 17 and, here, simultaneous DNA analyses and culturing would have facilitated learning.…”
Section: Discussionmentioning
confidence: 99%
“…While an NIPT test aims to diagnose chromosomal aberrations in fetal DNA, different chromosomal patterns in maternal DNA have been incidentally detected, which raised the suspicion of maternal malignancy [ 5 , 6 ]. The majority of these cancers were of hematologic origin, yet solid tumors, such as colorectal, gastric, breast and ovarian cancer, were also detected [ 5 , 6 , 7 ]. The recently published TRIDENT-2 study showed a prevalence of 70% maternal malignancy in individuals with two or more CNVs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%